PERBANDINGAN KINERJA ALGORITMA PROMETHEE DAN TOPSIS UNTUK PEMILIHAN GURU TELADAN - Bayu Firmanto; Harry Soekotjo; Hadi Suyono (Jurnal Penelitian Pendidikan IPA, 2016)
Department of Education has a mission to improve the quality of education by conducting quality improvement programs in aspects of facilities/infrastructure, curriculum, and the availability of qualified teachers. By conducting an exemplary teacher assessment, which aims to provide incentives to teachers to excel in the field of competence.Based on the he survey taken from City Education Department states that exemplary teacher assessment is currently done manually. Decision Support System is expected to improve performance and simplify the process of selection of candidates. In this study, the data exemplary teacher candidate selection used includes teacher data repot that contains the marks of the orientation of services, integrity, commitment, discipline, cooperation, leadership, performance and behavior. The proposed methods to solve the the exemplary teacher selection are PROMETHEE and TOPSIS methods.Based on the test performed showed that, the precision, recall, and accuracy parameter of the selection of the exemplary teacher candidates, have been produced 91.19%, 54.31% and 88.41% respectively for PROMETHEE method, and have been resulted 90.50% 74.91% and 94.34% respectively, for TOPSIS method. Therefore, the TOPSIS method has a better performance compared with the PROMETHEE method.Keywors: Calon guru teladan, sistem pendukung keputusan, metode PROMETHEEE, dan metode TOPSIS.